Heterogeneous grain structure in biodegradable Zn prepared via mechanical alloying and laser powder bed fusion for strength-plasticity synergy - Cijun Shuai; Yang Zhao; Youwen Deng; Chengde Gao (Virtual and Physical Prototyping, 2024)
ABSTRACTThis study presented a unique process of mechanical alloying (MA) and laser powder bed fusion (LPBF) to prepare heterogeneous grain structure (HGS) Zn with strength-plasticity synergy. The results showed that the MA-treatment significantly refined the grain sizes of Zn to nano-scale and contributed to the formation of HGS powders. Moreover, the ultra-fast heating and cooling of LPBF process inhibited the grain growth and resulted in a specific core/shell HGS, wherein the cores (micron-grains) were surrounded by interconnected shells (nano-grains). Notably, the prepared HGS Zn demonstrated synergistically improved compressive yield strength (2.1 times) and plasticity (58%) compared with the homogeneous coarse-grained counterparts. This impressive strength-plasticity synergy was primarily attributed to high back stress and dislocation pile-ups generated by the deformation incompatibility between the nano-grained shells and micron-grained cores. These findings open up new fields for MA and LPBF in the preparation of HGS metals and their applications in solving strength-plasticity tradeoff.